Photographic record of Cordyceps militaris (L.) Fr. occurrence in Barapathing Reserved Forest, Sikkim Himalaya - Chhetri, Prem Kumar; Rizal, Nagendra; chhetri, Bijoy (Indian Forester, 2025)
No Abstract.